Intrastate Variation in Treatment and Outcomes of Out-of-Hospital Cardiac Arrest. (2nd November 2018) - Coute, Ryan A.; Shields, Theresa A.; Cranford, James A.; Ansari, Sardar; Abir, Mahshid; Tiba, M. Hakam; Dunne, Robert; O'Neil, Brian; Swor, Robert; Neumar, Robert W.; ,
Abstract: Objective : Our objective was to analyze and compare out-of-hospital cardiac arrest (OHCA) system of care performance and outcomes at the Medical Control Authority (MCA) level in the state of Michigan. We hypothesized that clinically and statistically significant variations in treatment and outcomes of OHCA exists within a single U.S. state.Methods : We performed a retrospective, observational study of all non-traumatic EMS-treated OHCA from the state of Michigan CARES registry for 2014–2015. Geocoding of the OHCA incident address was used to assign records to individual MCAs. MCA-based demographics, arrest characteristics, system of care performance and outcomes were quantified and compared. Associations between demographics, system of care parameters, and outcomes were examined at the MCA level.Results : A total of 8, 115 records with complete data were available for analysis. Eleven MCAs met study inclusion criteria of >100 cases, producing a final sample size of 7, 788 records (96%). Statistically significant variations in survival to hospital discharge ranged from 4.5% to 15% (p < 0.001) (Adjusted odds ratio [AOR] range 0.6–2.0) and survival with good neurologic outcome 2.7–12.5% (p < 0.001; AOR range 0.5–2.2, ) were observed across MCAs. Bystander CPR ranged from 32% to 53% (p < 0.001) and bystander AED application ranged from 3.5% 11.5% (p < 0.05). Of patients admitted to the hospital alive, 29–68% received targeted temperature management. In hospital mortality ranged from 53.1% to 73.9% (p < 0.05).Conclusion : Significant intrastate variability in OHCA system of care performance and outcomes currently exist and are similar to what has been previously reported across North America almost a decade ago. This degree of variability highlights the opportunity to optimize modifiable factors within local systems of care to improve OHCA outcomes.